Correlation Between Physical Classroom Environment Temperature, Humidity, Noise and Students Learning Concentration Levels - Fluorina Oryza Muslim; Afridon (CV. Get Press Indonesia, 2026)
The classroom physical environment plays a critical role in shaping students’ learning concentration. Suboptimal conditions of temperature, humidity, and noise can reduce comfort and impair students’ ability to maintain focus during instructional activities. This study aimed to examine the relationship between classroom environmental factors (temperature, humidity, and noise) and learning concentration among senior high school students. An analytic observational study with a cross-sectional design was conducted involving 120 students from grades X and XI, selected through simple random sampling. Temperature and humidity were measured using a thermohygrometer, while noise levels were assessed with a sound level meter. Learning concentration was evaluated using a structured questionnaire. The questionnaire had been tested for validity and reliability (Cronbach’s alpha > 0.70), and ethical approval along with informed consent was obtained prior to data collection. Data were analyzed using univariate and bivariate approaches, with the Chi-square test applied at a significance level of 0.05. The findings indicated that most classroom conditions did not meet recommended standards, including temperature (58.3%), humidity (55.0%), and elevated noise levels (60.0%). Furthermore, the majority of students demonstrated low levels of learning concentration (56.7%). Bivariate analysis showed that temperature was not significantly associated with learning concentration (p = 0.231), whereas humidity (p = 0.002) and noise (p = 0.001) were significantly associated. In conclusion, humidity and noise are key determinants of students’ learning concentration, while temperature appears to have no significant effect. These findings underscore the importance of optimizing classroom environmental conditions to support effective learning.